Inventory Management in Precast Concrete Industry: A Strategic Study of Raw Material Management - Wahyu Ari Andriyanto; Gusti HG. Senoaji; Nita Dwi Cahyani (Majalah Ekonomi, 2025)
This study discusses the practice of raw material inventory management in a precast concrete company that uses an order-based production system. The aim is to evaluate the potential for implementing the Just in Time (JIT) concept to improve operational efficiency. This study uses a qualitative method with an ethnomethodology approach, through interviews, observations, and documentation to explore daily operational practices in depth. The results show that inventory management still depends on customer demand, but faces challenges such as repeated negotiations with vendors, testing materials before ordering, late delivery, stockpiling, and declining material quality. This condition causes high storage costs and reduces production efficiency. The ethnomethodology approach allows for an understanding of work routines and the meaning behind the actions of actors in the inventory system. This study assesses that the implementation of JIT can eliminate non-value-added activities, align material arrivals with production needs, and reduce costs. In addition, long-term contracts with vendors are considered effective in reducing repeated inspections and the risk of expired materials. Conceptually, this study enriches the literature by combining specific industries and methods that are rarely used in inventory management research.